Analysis of Left Atrial Performance in Patients with Type 2 Diabetes Mellitus without Overt Cardiac Disease and Inducible Ischemia: High Prevalence of Increased Systolic Force Related to Enhanced Left Ventricular Systolic Longitudinal Function. Issue 2 (12th May 2014) - Mazzone, Carmine; Cioffi, Giovanni; Faganello, Giorgio; Faggiano, Pompilio; Candido, Riccardo; Cherubini, Antonella; Tarantini, Luigi; De Feo, Stefania; Di Lenarda, Andrea
<x xml:space="preserve">Abstract</x> Objectives In patients with chronic pressure overload, higher left atrial systolic force (LASF) is associated with high‐risk cardiovascular (CV) phenotype, with increased left ventricular (LV) mass, concentric hypertrophy, and diastolic dysfunction. In hypertension and aortic stenosis, LASF predicts increased rate of CV events independent of traditional risk factors. Moreover, LASF is an independent predictor of heart failure in diabetic and nondiabetic patients. Limited data are available about LASF and its relationship with LV systolic function in type 2 diabetes mellitus (T2DM). Methods We used baseline clinic and echocardiographic data from 333 patients recruited in the SHORTWAVE study evaluating LV and left atrial performance in T2DM patients without cardiac disease. LASF was calculated by Manning's method and defined high when exceeded 16 Kdynes (90th percentile of LASF found in 120 healthy subjects used as controls). Results Mean LASF was 15.8 Â ± 9.4 Kdynes/cm2 and showed a close positive correlation with peak mitral annular systolic velocity (function of LV longitudinal fibers), independent of E/E′, age, systolic blood pressure, heart rate, and concentric geometry (multiple R = 0.57, P < 0.0001). Such independent correlation (tested in patients with and without concomitant hypertension) was confirmed at multiple logistic regression analysis where patients were dichotomized for having high (119 = 36%) or normal LASF. Conclusions High LASF is present in one third of T2DM patients without overt cardiac disease and is positively and independently related to an increased LV longitudinal shortening function, suggesting a close interaction between LV systolic and diastolic function.